2021
DOI: 10.1108/medar-06-2020-0922
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and CSR reporting: evidence from US companies and their Polish subsidiaries

Abstract: Purpose This study examines the internationalization effects of corporate social responsibility (CSR) reporting, specifically aiming to identify and compare the CSR reporting practices of large US multi-national corporations (MNCs) and their Polish subsidiaries. Design/methodology/approach Based on content analysis and using a disclosure index, the authors examined the CSR information posted on, or linked to, the corporate websites of a sample of 60 US-based MNCs and their subsidiaries operating in Poland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Recently, CSR has received attention due to its importance to customers, employees, shareholders, suppliers, the environment, and society as a whole. The practice of CSR is one of the effective ways by which an enterprise can enhance its reputation [2] and sharpen its competitive edge, which is subsequently reflected in a firm's profitability [3]. These days, in particular, with competition becoming increasingly tougher, CSR should be taken into consideration.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…Recently, CSR has received attention due to its importance to customers, employees, shareholders, suppliers, the environment, and society as a whole. The practice of CSR is one of the effective ways by which an enterprise can enhance its reputation [2] and sharpen its competitive edge, which is subsequently reflected in a firm's profitability [3]. These days, in particular, with competition becoming increasingly tougher, CSR should be taken into consideration.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…Further, they indicated the presence of agency effects as power and politics within the firms shaped their CSR activities (Bondy et al, 2012). Whereas Bondy et al (2012) investigated global firm headquarters, these issues would likely play out in their foreign subsidiaries as well (Cho et al, 2021), the topic the current study investigates.…”
Section: Literature Review and Research Proposition 21 Seeking And Ga...mentioning
confidence: 91%
“…Whereas Bondy et al. (2012) investigated global firm headquarters, these issues would likely play out in their foreign subsidiaries as well (Cho et al. , 2021), the topic the current study investigates.…”
Section: Literature Review and Research Propositionmentioning
confidence: 99%
“…A few fields of research in accounting are outlined and some examples of recent studies in these areas are shown for indicative purposes only. These includes research on the social impacts of accounting, including performance measurement (Power, 2015;Yang et al, 2021;Carnegie, 2022aCarnegie, , 2022b, the audit society (Jeacle and Carter, 2022), social and environmental accounting or sustainability accounting (Gray and Laughlin, 2012;Kaur and Lodhia, 2019;Lai and Stacchezzini, 2021;Atkins and McBride, 2022), corporate social responsibility (CSR) (Cho et al, 2021) and integrated reporting (Eccles and Krzus, 2010;Eccles and Saltzman, 2011;Dragu and Tiron-Tudor, 2014) and extending beyond such notions (de Villiers et al, 2022b(de Villiers et al, , 2022a as well as, more recently, the impacts of COVID-19 (Lodhia et al, 2021;Leoni et al, 2021Leoni et al, , 2022[2] Carnegie et al, 2022aCarnegie et al, , 2022d.…”
Section: Background and Informing Literaturementioning
confidence: 99%